2018
DOI: 10.13170/ajas.3.1.9632
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and regression analysis of the body measurements of the Doro Ncanga Buffalo (Bubalus bubalis) reared extensively in the Savanna of Mount Tambora Dompu Regency, Indonesia

Abstract: The objectives of the present study were to examine the correlation and regression of body measurements of the Doro Ncanga buffaloes in the savanna of Mount Tambora Dompu Regency, Indonesia. A total of 339 animals were used in this study. In female, body weight (BW) was found to be significantly (p<0.05) correlated with body length (BL), the degree of correlation increased from 0-6 (r=0.319) to 13-24 months (r=0.394), thereafter decreased at >36 months (r=0.160). The BW was not significantly correlated with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Male Anatolian buffaloes had higher means for CC, SD, BW and KG in comparison to female buffaloes ( Table 1 ) ( p < 0.01). Husni et al [ 27 ] determined the optimal regression model with BW, BL, HW and HG for the Doro Ncanga buffalo. They reported that the correlation between BW and BL, HW and HG was 0.319, 0.071 and 0.967, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Male Anatolian buffaloes had higher means for CC, SD, BW and KG in comparison to female buffaloes ( Table 1 ) ( p < 0.01). Husni et al [ 27 ] determined the optimal regression model with BW, BL, HW and HG for the Doro Ncanga buffalo. They reported that the correlation between BW and BL, HW and HG was 0.319, 0.071 and 0.967, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar population group, the average CG in buffaloes from SK according to Anggraeni et al (2011) was lower than in this study. In buffalo, the CG measurement has a high correlation with body weight (Dhillod et al 2017;Husni et al 2018;Eriani et al 2019). Murni et al (2020) obtained nine discriminant variables (with five functions) from eleven morphometrical measurements in buffaloes from Banten (Indonesia) with rc value of 0.81 (function 1).…”
Section: Discussionmentioning
confidence: 99%